2019
DOI: 10.31752/idea.2019.23
|View full text |Cite
|
Sign up to set email alerts
|

Cybersecurity in Elections: Models of Interagency Collaboration

Abstract: About one month before the 2019 North Macedonian presidential election, the State Election Commission's key information and communication systems did not function properly, which affected the timely accessibility of information; the publication of session minutes, instructions and decisions; the online verification of voters' data in the voter register; and the online register of complaints. This raised questions related to the commission's ICT security. According to the election commission, systems affected b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Depending on local regulations and customs, a technician or a trained optician may perform the exam. Moreover, an authoritative consumer report revealed that prescriptions issued by eye care professionals can have wide variability [25]. Importantly, although our Web-based refraction test depends on the patient’s input, it has zero variability with respect to interpreting the patient’s responses, and it should provide high test-retest reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Depending on local regulations and customs, a technician or a trained optician may perform the exam. Moreover, an authoritative consumer report revealed that prescriptions issued by eye care professionals can have wide variability [25]. Importantly, although our Web-based refraction test depends on the patient’s input, it has zero variability with respect to interpreting the patient’s responses, and it should provide high test-retest reproducibility.…”
Section: Discussionmentioning
confidence: 99%
“…Cyber threat actors could attempt to undermine citizens' opportunity to vote by tampering with election infrastructure [61]. This could be done, for instance, by disrupting electoral commissions via DDoS attacks or by compromising voting machines [62]. Such threats also imperil the secrecy of ballots.…”
Section: "Free and Fair" Electoral Processesmentioning
confidence: 99%